Oxygen and Carbon Isotopic Composition of Carbonate Rocks of the Permian Qixia Formation, Sichuan Basin: Thermal Effects of Emeishan Basalt - Keke Huang; Xiaoning Li; Zuowei Hu; Yijiang Zhong (Earth Sciences Research Journal)
The late Permian thermal events related to Emeishan Basalt has made a great impact on the underlying carbonate rock properties in the western margin of the Yangtze Platform. In this paper, we investigate the carbon and oxygen isotopic composition of the Qixia Formation carbonates from two sections: the Qiaoting Section in the northeastern part of the Sichuan Basin and the Changjianggou Section at the northwestern edge of the Basin. The data reveal that: (i) Samples from Qiaoting section show a relatively narrow range of δ13C and δ18O, varying from 2.7‰ to 5.2‰ with an average of 4.2‰, and -3.8‰ to -7.8‰ with an average of -5.4‰, respectively. In contrast, Samples from Changjianggou section exhibit larger magnitude of variation in δ13C and δ18O, ranging from -1‰ to 3.8‰ with an average of 1.5‰, and -2.1 to -9.2‰, with an average of -6.0‰ respectively; (ii) δ13C and δ18O records in carbonates from Qiaoting section are similar to those of Middle Permian seawater whereas carbonates from the Changjianggou section are depleted in 13C and 18O compared to contemporary seawater; (iii) On the basis of combined petrographic and paleo-heat flow evidence, the lower carbon and oxygen isotopic composition of the carbonates from the Changjianggou section are interpreted to be the results of thermal effects of Emeishan Basalt because of its proximity to the eruption center of the basalt. The high temperature reduced the δ18O values of the carbonates and forced the organic matter to mature at an early stage, thus producing 13C-enriched carbon dioxide to participate in the formation of carbonates.